Mini Quizzes in Elementary Mathematics Learning Assessment: Ujian Kecil dalam Penilaian Pembelajaran Matematika Dasar - Haq, Ghazwu Fikril; Faradita, Meirza Nanda; Martati, Badruli (Universitas Muhammadiyah Sidoarjo, 2026)
Basic mathematical operations are fundamental for numeracy learning in elementary education, yet many fourth-grade students still struggle with addition, subtraction, and multiplication, especially in complex tasks. Previous methods often focus on final results and rarely apply systematic formative assessment at the beginning of instruction to support both numeracy skills and learning effort. This study examined Mini Quizzes as an early formative assessment strategy for Grade IV students at SD Muhammadiyah 4 Pucang Surabaya. Using a quantitative one-group pretest–posttest design with 62 students, results showed a 36.34% improvement in basic operation skills, with the largest gain in multiplication (+73.85%). Learning effort, measured through summative score growth, increased by 17.47%, and effect sizes ranged from moderate to high. The study demonstrates the novelty of integrating Mini Quizzes routinely at the start of lessons to reinforce conceptual understanding and sustain learning effort. Mini Quizzes are therefore recommended as a practical tool to strengthen numeracy achievement and continuous mathematics learning outcomes in elementary schools. Highlights: Students demonstrated substantial growth in arithmetic skills after systematic early-session assessments. The strongest improvement occurred in higher-complexity multiplication tasks. Summative score progression reflected consistent increases in student learning effort. Keywords: Mini Quiz, Basic Mathematical Operations, Formative Assessment, Numeracy Elementary School